Condições materiais da imaginação criativa - Joaquim da Costa Leite (Carnets)
The time of Jules Verne (1828-1905) was a period of extraordinary change. The process of industrialization altered the systems of production, distribution and consumption, establishing the material conditions for the liberation of the imaginative creation of the human being.If the present was no longer just a repetition of the past, it was admissible to think that the future would be different from the present, thus opening the possibility of surpassing the barriers of traditional thinking.Within this historical framework, we find authors who, in the most diverse areas, demonstrated the exploration of radical ideas, hardly thinkable in 1800. Three examples, by chronological order: in 1848 Karl Marx and Friedrich Engels published the Manifesto of the Communist Party; in 1859 Charles Darwin published The Origin of Species; and Jules Verne began in 1863 the series which would become known as Extraordinary Voyages with the publication of Five Weeks in a Balloon.